Transforming society: the role and future of artificial intelligence - Iasechko, Svitlana (Review of Artificial Intelligence in Education, 2021)
In today’s world, artificial intelligence (AI) is becoming an increasingly important and influential field of research. It plays a key role in the development of technology, allowing the creation of intelligent systems and robots that can perform tasks that were once only possible for humans. In one of the facets of research in the field of AI, an important direction has been defined, which includes several main aspects. First, it is the development of formalization methods that allow presenting knowledge in a structured and logical form. This is necessary so that intelligent systems can effectively process and use this knowledge. Secondly, they are actively studying and formalizing reasoning in this direction. This includes understanding and modeling the processes of decision-making, logical thinking and information analysis. Thirdly, communication and dialogue between intelligent systems and people are explored. This is important for the development of interfaces and systems that can communicate with users in natural language and understand their needs and wishes. Fourthly, emphasis is placed on the development of algorithms to optimize the functioning of computing equipment and training of intelligent systems. This allows for improved productivity and efficiency of intelligent systems in various fields, from medicine and finance to transportation and manufacturing. In general, this line of research defines the key aspects of the development of artificial intelligence and is aimed at creating more intelligent and efficient intelligent systems that can make our lives more convenient and productive.